Proteomic profiling of renal tissue of normo- and hypertensive rats with the renalase peptide RP220 as an affinity ligand - Buneeva, O A; Fedchenko, V I; Kaloshina, S A; Zavyalova, M G; Zgoda, V G; Medvedev, A E (Biomeditsinskaia khimiia, 2024)
Renalase (RNLS) is a recently discovered protein that plays an important role in the regulation of blood pressure by acting inside and outside cells. Intracellular RNLS is a FAD-dependent oxidoreductase that oxidizes isomeric forms of β-NAD(P)H. Extracellular renalase lacking its N-terminal peptide and cofactor FAD exerts various protective effects via non-catalytic mechanisms. Certain experimental evidence exists in the literature that the RP220 peptide (a 20-mer peptide corresponding to the amino acid sequence RNLS 220-239) reproduces a number of non-catalytic effects of this protein, acting on receptor proteins of the plasma membrane. The possibility of interaction of this peptide with intracellular proteins has not been studied. Taking into consideration the known role of RNLS as a possible antihypertensive factor, the aim of this study was to perform proteomic profiling of the kidneys of normotensive and hypertensive rats using RP220 as an affinity ligand. Proteomic (semi-quantitative) identification revealed changes in the relative content of about 200 individual proteins in the kidneys of hypertensive rats bound to the affinity sorbent as compared to the kidneys of normotensive animals. Increased binding of SHR renal proteins to RP220 over the normotensive control was found for proteins involved in the development of cardiovascular pathology. Decreased binding of the kidney proteins from hypertensive animals to RP220 was noted for components of the ubiquitin-proteasome system, ribosomes, and cytoskeleton.